2015
DOI: 10.5897/ajest2014.1691
|View full text |Cite
|
Sign up to set email alerts
|

The effects of arbuscular mycorrhizal fungi and phosphorus levels on dry matter production and root traits in cucumber (Cucumis sativus L.)

Abstract: To evaluate the effect of arbuscular mycorrhizal fungi and phosphorus levels on root traits of cucumber plants, a factorial experiment was carried out based on a randomized completely design pot culture. Four phosphorus fertilization treatments, including 2, 5, 10 and 15 mg P kg-1 soil possessed phosphorus fertilization levels as the first factor. At the second factor arranged Glomus mosseae, Glomus intraradices of mycorrhiza species and non-inoculum as a control with three replications were conducted in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…These results confirm those of Marx et al 37 , who demonstrated that the more available the nitrogen and phosphorus in the soil, the less the roots mycorrhization. The mycorrhizal colonization under uninoculated plants (treatment T 0 ) was also low, confirming the ubiquitous inefficient native of fungi occurring naturally in most agricultural soils 38,39 . However, appropriate compost/soil ratio+AMF mycorrhiza increased the growth parameters of Allium sativum, in conformity with increased vegetative growth of Allium (plant height, number of leaves and other) following application of compost extract+biofertilizers 40 .…”
Section: Discussionmentioning
confidence: 81%
“…These results confirm those of Marx et al 37 , who demonstrated that the more available the nitrogen and phosphorus in the soil, the less the roots mycorrhization. The mycorrhizal colonization under uninoculated plants (treatment T 0 ) was also low, confirming the ubiquitous inefficient native of fungi occurring naturally in most agricultural soils 38,39 . However, appropriate compost/soil ratio+AMF mycorrhiza increased the growth parameters of Allium sativum, in conformity with increased vegetative growth of Allium (plant height, number of leaves and other) following application of compost extract+biofertilizers 40 .…”
Section: Discussionmentioning
confidence: 81%